1999
DOI: 10.1046/j.1365-2133.1999.02767.x
|View full text |Cite
|
Sign up to set email alerts
|

The extent and nature of disability in different urticarial conditions

Abstract: Chronic forms of urticaria are common, often adversely impacting on quality of life. No formal studies have assessed the extent and nature of disability in different types of urticaria. The Dermatology Life Quality Index (DLQI) is a simple and validated 10-item questionnaire designed to measure and compare disability in different skin conditions. In this study, we aimed to assess the disability in different urticarial groups using the DLQI, allowing comparison with previously published DLQI scores in common sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(145 citation statements)
references
References 15 publications
(24 reference statements)
8
129
2
6
Order By: Relevance
“…11,14 Studies have shown that the degree to which quality of life is affected in patients with chronic urticaria may vary in accordance with the different clinical types of the disease, and may in some aspects even become disabling. 15 The degree to which quality of life is impaired in these patients was found to be similar to that experienced by coronary patients with triple vessel coronary artery disease, principally with respect to psychological aspects and social relationships. 9 The objective of the present study was to assess the impact of chronic urticaria on patients' quality of life and to clarify which domains were more severely affected in these patients.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…11,14 Studies have shown that the degree to which quality of life is affected in patients with chronic urticaria may vary in accordance with the different clinical types of the disease, and may in some aspects even become disabling. 15 The degree to which quality of life is impaired in these patients was found to be similar to that experienced by coronary patients with triple vessel coronary artery disease, principally with respect to psychological aspects and social relationships. 9 The objective of the present study was to assess the impact of chronic urticaria on patients' quality of life and to clarify which domains were more severely affected in these patients.…”
Section: Introductionmentioning
confidence: 75%
“…These findings are in agreement with data published in the literature. 15,28,30 In the present study, the SF-36 domains indicative of greater impairment of quality of life were: rolephysical and vitality. The role-physical domain reflects 24,26 In the comparison of the scores of the questionnaires between the clinical types of chronic urticaria (COU, PU and MU), no statistically significant differences were found between the various types and it was impossible to conclude whether one may affect quality of life to a greater extent than another.…”
Section: 28-30mentioning
confidence: 98%
See 2 more Smart Citations
“…Además, entre los pacientes afectados se ha observado un incremento del factor de necrosis tumoral alfa (TNF-α) y de la interleucina 1-beta (IL-1β) en suero y en las capas basales de la epidermis no afectada. También, se ha sugerido que los derivados del ácido araquidónico están implicados, pero esto no se ha podido comprobar (12,14). También, se han asociado otros neuropéptidos, como la sustancia P y el péptido relacionado con el gen de la calcitonina.…”
Section: Urticaria Por Presiónunclassified